THE FLATULENCE SYMPTOM IN SMALL CHILDREN: CAUSES AND WAYS OF CORRECTION - A. N. Surkov; V. V. Chernikov (Педиатрическая фармакология)
Gastrointestinal tract malfunctions, food allergy, intestinal microbiocenosis disorder, disaccharide insufficiency, celiac disease and several other causes lead to an increased gas-formation, overdistension of intestinal loops and abdominal pains in 0-1-year-old children. The crucial task of flatulence elimination is the correction of causes of its occurrence. Frequent intestinal spasm episodes in infants reduce the quality of life of them and their families in general and are also associated with the subsequent child’s physical and mental maldevelopments. Simethicone-based suspension (in the form of antifoaming agent) helps to cope with the issue; it has carminative properties; this allows to reduce the amount of gases in the intestinal lumen, thus terminating pain symptoms.